Tumor contact length of prostate cancer determined by a three‐dimensional method on multiparametric magnetic resonance imaging predicts extraprostatic extension and biochemical recurrence. (5th July 2021) - Miyamoto, Shunsuke; Goto, Keisuke; Honda, Yukiko; Terada, Hiroaki; Fujii, Shinsuke; Ueno, Takeshi; Fukuoka, Kenichiro; Sekino, Yohei; Kitano, Hiroyuki; Ikeda, Kenichiro; Hieda, Keisuke; Inoue, Shogo; et al.
Abstract : Objective: To evaluate the clinical benefit of tumor contact length as a predictor of pathological extraprostatic extension and biochemical recurrence in patients undergoing prostatectomy. Methods: A total of 91 patients who underwent 3T multiparametric magnetic resonance imaging before prostatectomy from April 2014 to July 2019 were included. A total of 94 prostate cancer foci were analyzed retrospectively. We evaluated maximum tumor contact length, which was determined to be the maximum value in the three‐dimensional directions, as a predictor of pathological extraprostatic extension and biochemical recurrence. Results: A total of 19 lesions (20.2%) had positive pathological extraprostatic extension. Areas under the curves showed maximum tumor contact length to be a significantly better parameter to predict pathological extraprostatic extension than the Prostate Imaging Reporting and Data System ( P  = 0.002), tumor maximal diameter ( P  = 0.001), prostate‐specific antigen ( P  = 0.020), Gleason score ( P  < 0.001), and clinical T stage ( P  < 0.001). Multivariate analysis showed maximum tumor contact length ( P  = 0.003) to be an independent risk factor for predicting biochemical recurrence. We classified the patients using preoperative factors (prostate‐specific antigen >10, Gleason score >3 + 4 and maximum tumor contact length >10 mm) into three groups: (i) high‐risk group (patients having all factors); (ii) intermediate‐risk group (patients having two of three factors); and (iii) low‐risk group (patients having only one or none of the factors). Kaplan–Meier curves showed that the high‐risk group had significantly worse biochemical recurrence than the intermediate‐risk group ( P  = 0.042) and low‐risk group ( P  < 0.001). Conclusions: Our findings suggest that maximum tumor contact length is an independent predictor of pathological extraprostatic extension and biochemical recurrence. A risk stratification system using prostate‐specific antigen, Gleason score and maximum tumor contact length might be useful for preoperative assessment of prostate cancer patients.